Influence of Job and Salary on Job Satisfaction on Nurses in Special Inpatient Units - Fernanda, Anggela Vetania; Nisa, Fauziyatun; Anggraini, Fritria Dwi; Munjidah, Annif; Novianti, Hinda (International Journal of Psychosocial Rehabilitation, 2026)
The nurse will provide good services to the patient when the nurse satisfied at work. RSI Jemursari Surabaya there is no measurement of job satisfaction on nurses. The results of the preliminary studies to 14 nurses obtained 11 nurses satisfied and 3 nurses are less satisfied. This research aims to analyze influence of job and salary on job satisfaction on nurses in Special Inpatient Units RSI Jemursari. This type of research uses an analytic survey with a cross-sectional approach. Sampling using cluster random sampling with a large sample of 89 nurses consists of IBS, HD, ICU, and IGD-Resuscitation Ambulance. Data collection techniques using primary data by the method of a questionnaire. Data analysis using the binary logistic regression test. The results showed almost exclusively nurses have jobs (95.5%), and salary (92.1%) Accordingly and have satisfaction in work (93.3%). Test results obtained jobs (0.026) and salary (0.048) have an impact on job satisfaction. The conclusion that is job satisfaction will increase in jobs and salaries accordingly. Advice may be given that is expected to improve hospital management on the job satisfaction of nurses in particular nurses Special Inpatient Units. This is done by giving a better income and work they do allow to be able to use the capability.